Respuesta :
Answer:
[tex]\sf m=-4 \frac{3}{5}[/tex]
Step-by-step explanation:
[tex]\sf -3=1 \frac{3}{5}+m[/tex]
[tex]\sf \implies -3=1+\dfrac{3}{5}+m[/tex]
Subtract 1 from both sides:
[tex]\sf \implies -3-1=1+\dfrac{3}{5}+m-1[/tex]
[tex]\implies \sf -4=\dfrac{3}{5}+m[/tex]
Subtract 3/5 from both sides:
[tex]\implies \sf -4-\dfrac{3}{5}=\dfrac{3}{5}+m-\dfrac{3}{5}[/tex]
[tex]\implies \sf -4-\dfrac{3}{5}=m[/tex]
[tex]\implies \sf -\left(4+\dfrac{3}{5}\right)=m[/tex]
[tex]\implies \sf m=-4 \frac{3}{5}[/tex]